2006
DOI: 10.1111/j.1365-2486.2006.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential of cropping systems and soil amendments for carbon sequestration in soils under long‐term experiments in subtropical India

Abstract: An understanding of the dynamics of carbon (C) stock in soils, as impacted by management strategies, is necessary to identify the pathways of C sequestration in soils and for maintaining soil organic C (SOC) at a level critical for upkeeping soil health and also for restraining global warming. This is more important in tropical and subtropical region where soils are inherently low in organic C content and the production system is fragile. We evaluated the long-term role of crop residue C inputs to soil in SOC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(125 citation statements)
references
References 21 publications
7
104
3
1
Order By: Relevance
“…Double rice cultivation needs intensive tillage, puddling thereby destroying soil structure, and subsequently affecting distribution and stability of the aggregates (Six et al, 2002) which resulted in declining carbon content of soils. Our results are in line with Mandal et al, (2007) and Majumder et al, ( , 2008 who reported similar magnitude of SOC depletion (2-15% of fallow). .…”
Section: Sequestrationsupporting
confidence: 82%
“…Double rice cultivation needs intensive tillage, puddling thereby destroying soil structure, and subsequently affecting distribution and stability of the aggregates (Six et al, 2002) which resulted in declining carbon content of soils. Our results are in line with Mandal et al, (2007) and Majumder et al, ( , 2008 who reported similar magnitude of SOC depletion (2-15% of fallow). .…”
Section: Sequestrationsupporting
confidence: 82%
“…This observation is in line with results of other studies showing the addition of exogenous organic matter like compost resulting in an enhancement of soil organic carbon storage in addition to improvement of many functions related to the presence of organic matter (Lashermes et al, 2009, Okae-Anti et al, 2013. In tropical soils, the impact of organic amendment on long-term carbon storage might be rather small (Mandal et al, 2007). However, many studies noted their beneficial effects on nutrient cycling (Ngo et al, 2012;Kaur et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several model simulation studies have analysed the influence of increased CO 2 future scenarios on monsoon dynamics and precipitation (Cherchi et al, 2011;May 2011;Meehl and Washington, 1993;Meehl et al, 2000). Furthermore, other studies have shown that tropospheric CO 2 concentrations can be influenced by the strength of the monsoon and El Niño circulations (Mandal et al, 2006;Jiang et al, 2010;Schuck et al, 2010;Wang et al, 2011). Tiwari et al (2011) andBhattcharya et al (2009) have shown effects of the Indian summer monsoon on the distribution of atmospheric CO 2 .…”
Section: Introductionmentioning
confidence: 99%